AB0136 In Vitro Induced Regulatory T-Cells Can Reduce Severity of Lupus Arthritis. (15th July 2016) - Leiss, H.; Jacobs, B.; Gessl, I.; Puchner, A.; Niederreiter, B.; Steiner, C.W.; Smolen, J.; Stummvoll, G.
Abstract : Background: Even though joint involvement is a major burden in patients suffering from systemic lupus erythematosus (SLE), it is not focus of scientific research and treatment strategies continue to be limited. Studying lupus arthritis and possible treatment options can be done with the murine model of Pristane-induced lupus (PIL). Objectives: We herein investigate if in vitro induced regulatory T-cells ( i Treg) are capable of ameliorating PIL arthritis and help us evaluate possible new treatment options. Methods: BALB/c mice were injected i.p. with either 0.5ml of pristane (PIL-group) or PBS (controls). Naive CD4 + thymocytes were sorted and cultured and cell suspensions with >80% of CD4 + FoxP3 + cells ( i Treg) were injected intravenously (i) once when PIL was induced (5x10 6 i Treg, i Treg-boost), or (ii) every 4 weeks (1x10 6 i Treg, i Treg-rep). Animals were monitored for paw swelling and grip strength. After 8 months histological analysis evaluated for cartilage degradation, number of osteoclasts and the extent of inflammation and bone erosion. In addition, the cellular composition of the inflammatory tissue was determined by a cell-identification algorithm for nuclear segmentation (HistoQuest). Serum levels of anti-dsDNA, anti-histone and anti-chromatin antibodies were measured by ELISA. Results: Monthly injections of 1x10 6 i Treg reduced the clinical as well as the histological severity of PIL-arthritis, seen by a higher mean grip strength (2.964±0.024 vs. 2.732± 0.063, p<0.01), less mean paw swelling (0.044±0.020 vs. 0.360 ±0.069) and retardation of the symptom onset. 62% of PIL-mice and 33% of i Treg-rep mice had erosive arthritis. There was a significant reduction of arthritis severity in all histological parameters (inflammatory area 0.188±0.0574 vs. 0.688±0.113; erosive area 0.011 ±0.009 vs. 0.069±0.017; number of osteoclasts 2.000± 1.125 vs. 9.143±1.999; cartilage degradation 0.059±0.004 vs. 0.187±0.033). The single boost of 5x10 6 i Treg could not prevent joint manifestation. However, a slight retardation in "loss of grip strength" and a significantly less erosive area was seen. In regards to the cellular composition of the inflammatory tissue, a significantly increased relative amount of Foxp3 cells was seen in the i Treg-rep group compared to the PIL group (5.2±2.3 vs. 0.6±0.2). Corresponding to the reduced severity in joint involvement, the i Treg-group had significantly lower serum levels of antibodies. Conclusions: Repeated injections of i Treg ameliorate the clinical and histological severity of PIL- arthritis. A single boost of i Treg at the time of disease induction does not prevent joint manifestation, but retards the onset of symptoms and progression of erosive bone degradation. Thus, i Treg have significant positive effects on PIL arthritis, which may have consequence for future therapeutic considerations. Disclosure of Interest: None declared